Teacher Performance from the Perspective of Goal Setting Theory: The Influence of Competence, Work Culture, Motivation, Job Satisfaction, and Work Environment - Oddy Irvanto Fatariska; Suryo Budi Santoso; Sri Wahyuni; Hengky Widhiandono (Universitas KH. Abdul Chalim Mojokerto, 2026)
Teacher performance plays a crucial role in determining the quality of education. Although some teachers have demonstrated good performance, issues such as low discipline, lack of participation, and weak collaboration among teachers are still found. This study investigates how competence, work culture, motivation, job satisfaction, and work environment affect the performance of teachers at Muhammadiyah high schools in Banyumas Regency. This study involved 149 teachers from Muhammadiyah high schools in Banyumas Regency. A quantitative survey method was used to analyze the SEM-PLS data after collecting data through an online questionnaire. The results show that competence, work culture, and work motivation do not have a significant effect. In contrast, job satisfaction and work environment have a positive and significant influence on teacher performance. These findings highlight that psychological and environmental aspects are more decisive in improving teacher performance than technical factors. In line with Goal Setting Theory, environmental support and individual satisfaction are key to achieving work goals. Practically, these results imply that Muhammadiyah schools should focus more on creating a healthy work environment and improving teacher well-being. Theoretically, this research also enriches the development of performance models based on psychosocial aspects.